Electronic Structure Methods for Large Molecular Systems and Materials in Strong Magnetic Fields - Speake, Benjamin (2023)
The high-rank polynomial scaling of modern electronic structure methods can present significant limitations on the size of molecular systems that can be accurately studied. This issue is further exasperated when using non-perturbative approaches for studying systems within arbitrary strength magnetic fields due to the requirements for complex algebra and reduced permutational symmetry. One such attempt at overcoming this issue is the concept of fragmentation, which has shown promise in recent years for accurately determining the electronic structure of systems that can be sensibly fragmented into smaller subunits. The main aim in this work is to combine the concepts of one such method, the embedding fragment method (EFM), with recent advances in non-perturbative treatment of external fields, enabling the study of increasingly large or complex systems. The implementation of this approach is presented for systems in strong magnetic fields. The method is applied to determine energetic, structural and magnetic response properties of systems beyond the scope of more conventional methods. The EFM is shown to provide an accurate electronic structure approximation when studying systems within extremely strong magnetic fields, with errors generally < 0:001% compared to conventional all electron methods, maintaining accuracy up to fields on the order of >70000 Tesla. Its application to large water clusters is presented showing how external magnetic fields strengthen intermolecular interactions, as has previously been demonstrated through experiment, but that the origin of this strengthening is not as straightforward as the altering of the hydrogen bonding present at zero field, a rational often considered alongside experimental results. Also demonstrated is how this approach can be used to accurately model solvation effects when calculating magnetic properties of solute molecules. In this work the calculation of nuclear magnetic resonance chemical shifts is considered, using the EFM and comparing to both gas phase calculations and calculations including solvent effects using the polarisable continuum method. To aid in the interpretation of results, two additional tool sets have been development. The first is a suite of tools to analyse the complex current vector field induced by exposing a molecule to an external field. The second is a new molecular viewer software package, improving the ability to analyse the effects of external magnetic fields on molecular systems.